TRIPARTITE COLLABORATION BETWEEN TVRI, KPU, AND BAWASLU IN ACCOUNTABILITY IN THE IMPLEMENTATION OF THE 2024 REGIONAL ELECTIONS - Lesawengen, Mineshia; Niode, Burhan; Pangemanan, Fanley N; Liando, Daud M, Liando; Lengkong, Johny P, (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2026)
The simultaneous 2024 Regional Election (Pilkada) in North Sulawesi faced complex challenges of accountability, transparency, and integrity across an archipelagic region with 15 regencies/cities where 320 violation reports were recorded. This study aims to analyze the tripartite collaboration model among TVRI North Sulawesi, KPU North Sulawesi Province, and Bawaslu North Sulawesi Province in strengthening accountability of the 2024 Pilkada. A qualitative case study approach was employed using Emerson and Nabatchi’s (2015) Collaborative Governance Regime (CGR) framework and Rhodes’s (1997) Policy Network Theory, conducted during August–December 2024 through in-depth interviews with key informants and documentation review, with data analysis following Miles and Huberman’s interactive model and triangulation for validity. Results show that tripartite collaboration functioned effectively despite the absence of a formal legal framework, anchored in resource interdependence awareness, internalized democratic culture, mutual trust, and commitment to shared goals, with a triangular interdependence pattern creating intrinsic incentives for collaboration that produced a voter participation rate of 76.8%, surpassing the national average. It is concluded that a flexible institutionalization approach combining informal flexibility with selective formalization in critical aspects is needed to ensure collaboration sustainability in future elections, while contributing a triangular interdependence model to the collaborative governance literature in the Indonesian context